Testing the Monetary Model for Exchange Rate Determination in South Africa: Evidence from 101 Years of Data - Riané de Bruyn; Rangan Gupta; Lardo Stander (Contemporary Economics, 2013)
Evidence in favor of the monetary model of exchange rate determination for the South African Rand is, at best, mixed. A co-integrating relationship between the nominal exchange rate and monetary fundamentals forms the basis of the monetary model. With the econometric literature suggesting that the span of the data, not the frequency, determines the power of the co-integration tests and the studies on South Africa primarily using short-span data from the post-Bretton Woods era, we decided to test the long-run monetary model of exchange rate determination for the South African Rand relative to the US Dollar using annual data from 1910 - 2010. The results provide some support for the monetary model in that long-run co-integration is found between the nominal exchange rate and the output and money supply deviations. However, the theoretical restrictions required by the monetary model are rejected. A vector error-correction model identifies both the nominal exchange rate and the monetary fundamentals as the channel for the adjustment process of deviations from the long-run equilibrium exchange rate. A subsequent comparison of nominal exchange rate forecasts based on the monetary model with those of the random walk model suggests that the forecasting performance of the monetary model is superior.
Keywords: C22; C32; C53; F31; F47; 330; nominal exchange rate; monetary model; long-span data; forecasting